Interrelationships of parental belief, parental investments, and child development: A cross-sectional study in rural China. (November 2020) - Zhong, Jingdong; Gao, Jingjing; Wang, Tianyi; He, Yang; Liu, Chengfang; Luo, Renfu
Highlights: Parental belief is associated with Child social-emotional development. Parental investments mediate parental belief and child development. The mediation effects vary across investments and developmental outcomes. The varieties of play materials and activities are the strongest mediators. Abstract: Background: Parental investments are associated with early child outcomes, and some evidences outside China suggest that parental belief might affect parental investments. However, the interrelationships of parental belief, parental investments, and early child development has not been well documented in China. Aims: This paper aims to study the interrelationships between the caregiver's parental belief, the caregiver's parental investments, and the child's early developmental outcomes in rural China. Methods: A total of 1787 sample households in an undeveloped rural area of western China are enrolled in the cross-sectional study. A parental belief questionnaire, the Family Care Indicators (FCI), the Bayley Scales of Infant Development version III (BSID-III), and a socioeconomic questionnaire were used to measure the caregiver's parental belief on parenting practices, the caregiver's parental investments, the child's early developmental outcomes, and the socioeconomic characteristics of sample households, respectively. The mediation model was then applied to estimate the interrelationships. Results: The results find that the caregiver's parental investments significantly mediate in the relationships between the caregiver's parental belief and the child's early developmental outcomes. Through parental investments, one standard deviation (SD) increase in the caregiver's parental belief is corresponding to 3% of one SD increase in the child's four developmental outcomes (cognition, language, motor, and social–emotion) respectively. Conclusions: For future studies aimed at designing targeted interventions on early child development in rural China, the key findings of this paper might be informative. Early interventions aimed at strengthening the caregiver's subjective belief on parenting practices and increasing the parental investments in the household might be effective to improve the development of rural children.